Etiology Exploration of Non-alcoholic Fatty Liver Disease From Traditional Chinese Medicine Constitution Perspective: A Cross-Sectional Study - Zhu, Ke; Guo, Yongsong; Zhao, Chenghao; Kang, Shixin; Li, Jialiang; Wang, Jiexin; Tang, Zhaohui; Lin, Bing; Li, Weihong (Frontiers in Public Health, 2021)
Background: From the traditional Chinese medicine (TCM) constitution theory perspective, the phlegm-dampness constitution is thought to be closely related to the occurrence of non-alcoholic fatty liver disease (NAFLD). However, this viewpoint still lacks rigorous statistical evidence. This study aimed to test the association between the phlegm-dampness constitution and NAFLD. Methods: We conducted a cross-sectional study. Participants were residents living in Chengdu, China, undergoing health checkups at the health management center of Affiliated Hospital of Chengdu University of Traditional Chinese Medicine between December 2018 and September 2020. TCM constitution type was diagnosed by DAOSH four examinations instrument, NAFLD was diagnosed according to the liver ultrasonography and medical history. Multivariate logistic regression and propensity score matching (PSM) were used to analyze a total of 1,677 qualified data. Results: 1,037 participants had biased constitution(s), 67.8% of which had mixed constitutions (with at least two constitutions). Among 1,677 participants, the phlegm-dampness constitution was associated with the yang-deficiency, yin-deficiency, dampness-heat, qi-depression, and blood-stasis constitutions. The correlation coefficients were 0.11, 0.32, 0.42, 0.20, 0.14, respectively. Between the phlegm-dampness constitution and NAFLD, the odds ratio (OR) and the 95% confidence interval (CI) was 2.05 (1.57–2.69) in the crude model. After adjusting for age, gender, Body mass index (BMI), other biased constitutions, smoking, high blood pressure, diabetes, and dyslipidemia, the OR reduced to 1.51 (1.04–2.18). The associations of seven other biased TCM constitutions and NAFLD were not statistically significant in the fully adjusted model. The PSM analysis showed consistent results with the logistic regression. Conclusions: Among eight biased TCM constitutions, the phlegm-dampness constitution is independently associated with NAFLD. We speculate the phlegm-dampness constitution is a risk factor of NAFLD. Longitudinal studies are needed to confirm this causal relationship in the future. In addition, inconsistent with some TCM practitioners' experience, we disagree that the blood-stasis constitution is associated with NAFLD.